Political Conflict as an Ideological Influential Agent in the Iraqi Rural Novel - Mutlaq, Dunya Hashim Ibraheem; Al-Dbow, Aysar Mohammed Fadhil (Dirasat: Human and Social Sciences, 2024)
Objectives:The study aims to examine the political conflict as an influential agent of ideology. It also aims to explore what lies behind the Iraqi narrative text and the societal consequences it carries that found a fertile land in the Iraqi countryside, which was the arena for achieving gains and interests and the emergence of classes. Methods:The study adopts the critical, cultural, analytical approach which is based on employing what is implicit and analyzing what is hidden through deep analysis based on studying political contexts as one of the factors surrounding the text, in addition to the social, religious, and cultural factors. Results:The study concluded that Marxism in its communism form is - as it seems - the most effective ideology in terms of its adoption by the great novelists because it was in harmony with the Iraqi environment which is prepared to accept the concepts of this philosophy. Class was prevalent in the countryside, and the political conflict in the rural novel comes in various narrative forms; it might be direct and clear, or an insinuation through references to spaces and places with implications for establishing the conflict. Conclusions:The study is based on addressing the political effect of ideological references on the individual and its reflections on the conflict between individuals’ aspirations for freedom and building social peace for the peasant class and rural life and the other; exploitation and control according to an agenda and references that attempt to control the society which represent the opposition of these aspirations.